Evaluating chronic emotional dysregulation and irritability in relation to ADHD and depression genetic risk in children with ADHD. (12th October 2019) - Nigg, Joel T.; Karalunas, Sarah L.; Gustafsson, Hanna C.; Bhatt, Priya; Ryabinin, Peter; Mooney, Michael A.; Faraone, Stephen V.; Fair, Damien A.; Wilmot, Beth
Abstract : Background: A central nosological problem concerns the etiological relationship of emotional dysregulation with ADHD. Molecular genetic risk scores provide a novel method for informing this question. Methods: Participants were 514 community‐recruited children of Northern European descent age 7‐11 defined as ADHD or non‐ADHD by detailed research evaluation. Parents‐rated ADHD on standardized ratings and child temperament on the Temperament in Middle Childhood Questionnaire (TMCQ) and reported on ADHD and comorbid disorders by semi‐structured clinical interview. Categorical and dimensional variables were created for ADHD, emotional dysregulation (implicating disruption of regulation of both anger‐irritability and of positive valence surgency‐sensation seeking), and irritability alone (anger dysregulation). Genome‐wide polygenic risk scores (PRS) were computed for ADHD and depression genetic liability. Structural equation models and computationally derived emotion profiles guided analysis. Results: The ADHD PRS was associated in variable‐centered analyses with irritability (β = .179, 95% CI = 0.087–0.280; Δ R 2  = .034, p  < .0002), but also with surgency/sensation seeking (B = .146, 95%CI = 0.052–0.240, Δ R 2 =.022, p  = .002). In person‐centered analysis, the ADHD PRS was elevated in the emotion dysregulation ADHD group versus other ADHD children (OR = 1.44, 95% CI = 1.03–2.20, Nagelkerke Δ R 2  = .013, p  = .033) but did not differentiate irritable from surgent ADHD profiles. All effects were independent of variation in ADHD severity across traits or groups. The depression PRS was related to oppositional defiant disorder but not to ADHD emotion dysregulation. Conclusions: Irritability‐anger and surgency‐sensation seeking, as forms of negative and positively valenced dysregulated affect in ADHD populations, both relate principally to ADHD genetic risk and not mood‐related genetic risk.